Locally Differentially Private and Consistent Frequency Estimation of Longitudinal Data - Marreiras Neto, Antonio A.; Duarte Neto, Eduardo R.; Costa Filho, José S.; Machado, Javam C. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
Local Differential Privacy (LDP) was developed as a Differential Privacy (DP) model that protects user data from the collector. However, tasks such as frequency estimation over time are challenging to apply LDP guarantees to, as privacy and utility goals are subjected to increasing privacy budget consumption. Utility can be enhanced through post-processing techniques, but it's important to be aware that they may introduce unintended bias. In this paper, we analyze the performance of a range of longitudinal LDP protocols coupled with various post-processing techniques, of which we determined Norm Sub and PowerNS to be the best-performing and warned against the use of Norm Mul.